2017
DOI: 10.2175/106143016x14798353399412
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Year Microbial Source Tracking Study Characterizing Fecal Contamination in an Urban Watershed

Abstract: Microbiological and hydrological data were used to rank tributary stream contributions of bacteria to the Little Blue River in Independence, Missouri. Concentrations, loadings and yields of E. coli and microbial source tracking (MST) markers, were characterized during base flow and storm events in five subbasins within Independence, as well as sources entering and leaving the city through the river. The E. coli water quality threshold was exceeded in 29% of base-flow and 89% of storm-event samples. The total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…PCR detection showed a chronic presence of a mammalian fecal source(s) (100% of samples), with a human fecal source(s) detected in approximately half of all samples; thus, qPCR analysis is useful for bringing context to the significance of these findings. For example, Mayer et al (47) showed that wastewater effluent contains approximately 10 8 copies/100 ml of the AllBac mammal fecal marker, Sowah et al (48) found that streams impacted by septic systems contained 10 5 to 10 7 copies/100 ml depending on the season, and Bushon et al (49) determined that under storm flow conditions in an urban watershed, mammal marker copy numbers exceeded 10 8 copies/100 ml. Results for this study ranged from 10 5 to 8.6 ϫ 10 7 copies/100 ml, values that are within previously reported ranges and likely concentrations reflective of a predominantly nonurbanized watershed and intermediate mammal source loading.…”
Section: Discussionmentioning
confidence: 99%
“…PCR detection showed a chronic presence of a mammalian fecal source(s) (100% of samples), with a human fecal source(s) detected in approximately half of all samples; thus, qPCR analysis is useful for bringing context to the significance of these findings. For example, Mayer et al (47) showed that wastewater effluent contains approximately 10 8 copies/100 ml of the AllBac mammal fecal marker, Sowah et al (48) found that streams impacted by septic systems contained 10 5 to 10 7 copies/100 ml depending on the season, and Bushon et al (49) determined that under storm flow conditions in an urban watershed, mammal marker copy numbers exceeded 10 8 copies/100 ml. Results for this study ranged from 10 5 to 8.6 ϫ 10 7 copies/100 ml, values that are within previously reported ranges and likely concentrations reflective of a predominantly nonurbanized watershed and intermediate mammal source loading.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, multiple WMPs performed source tracking studies, which have been indicated to be on the forefront of water quality analyses (Bushon et al. ). Microbial source tracking and fluorometry (fluorescence spectroscopy) monitoring are among the types of source tracking used.…”
Section: Resultsmentioning
confidence: 99%
“…PCR detection showed a chronic presence of mammalian fecal source(s) (100% of samples) with human fecal source(s) detected in approximately half of all samples, so qPCR analysis is useful for bringing context to the significance of these findings. For example, Mayer et al (47) showed that wastewater effluent contains about 10 8 copies/100 ml of the AllBac mammal fecal marker, Sowah et al (48) found that streams impacted by septic systems could contain 10 5 – 10 7 copies/100 ml depending on the season, and Bushon et al (49) determined that under storm flow conditions in an urban watershed mammal marker copy numbers could exceed 10 8 copies/100 ml. Results for this study ranged from 10 5 to 8.6 × 10 7 copies/100 ml, values that are within previously reported ranges and likely a concentration reflective of a predominantly non-urbanized watershed and intermediate mammal source loading.…”
Section: Discussionmentioning
confidence: 99%